Study on fauna, biology and ecology of Miridae (Hemiptera-Heteroptera) in agro-biocenosis and natural ecosystems of Uzbekistan - Boltaboev Adamboy; Mamarakhimov Oybek; Islamov Avaz; Kuchkarov Tukhtamurod; Tursunov Diyor (BIO Web of Conferences)
Agricultural production is a critical asset contributing to the economic development of numerous countries with arid and semi-arid climatic characteristics. In recent years, however, the world has witnessed significant losses in agriculture due to the negative impact of pests on crops. Therefore, the accurate assessment impact of agricultural pests on crop production is necessary. However, this could be challenging without proper investigations on their biological and ecological characteristics in data scarce regions, including Uzbekistan. To fulfill this scarcity, this study explores the fauna, biology and ecology of Miridae (Hemiptera- Heteroptera) species prevalent in agro-biocenosis and natural ecosystems of Uzbekistan. To better understand their biological and ecological characteristics, we performed field observations on 8 regions of Uzbekistan. The results indicated that three families (Miridae Hahn 1833, Nabidae Costa 1852, Antocoridae Fiber 1837), 6 generas and 20 species of blind (Miridae) are widespread in the selected regions.